Successful treatment with sorafenib in patients with advanced hepatocellular carcinoma: clinical case - Yu V Bisovskaya (Современная онкология, 2014)
Multi-kinase inhibitor sorafenib is the only one drug which increases life time in patients with advanced hepatocellular carcinoma (HCC). Results from the SHARP trial showed that median progression-free survival was less than 5 months. However, it is possible to achieve strong treatment effect for several years receiving sorafenib. Antiviral treatment in the course of the immune treatment for all patients with chronic hepatitis B (CHB) should follow the recommendations from existing The European Association for the Study of the Liver (EASL) guidelines. It is possible to prescribe constant antiviral therapy (AT) with the nucleosides analogue as a treatment (according to the indication) or for prophylactic purposes (prevention of reactivation of HBV-infection in «inactive HBsAg carriers») to prevent cirrhosis development and to prolong sorafenib therapy. New multi-kinase inhibitor sorafenib was approved for the treatment of advanced HCC in the Russian Federation (RF) in 2006. However, there is not enough information on receiving sorafenib in patients with HCC associated with CHB in the RF. Our clinical case presents long-term treatment (37 months) with sorafenib in the course of the AT in patients with HCC. This example helps us to discuss the features of modern diagnostic and treatment algorithm of HCC, chronic hepatitis B and cirrhosis in its outcome.